Protection of human rights. Aspects regarding maritime piracy - Nicolau, Ingrid Ileana; Marin, Marilena (Technium Social Sciences Journal, 2022)
Maritime piracy represents a strange reality in a world that considers itself evolved, without primitivism and medieval cruelty. However, the obsolescence of these iniquities often stops the cruel reality to come to surface, namely the fact that the danger and ferocity of these acts could generate unpredictable evolutions able to affect more and more areas of the Planetary Ocean. The implementation of comprehensive international legislation in this area and the allocation of necessary forces and means to combat this scourge are becoming increasingly acute if we take into account the fact that the methods and, especially, the means of carrying out maritime piracy and armed robbery at sea are more and more performing, since pirates and sea robbers have been endowed with the latest communications equipment, ultra-fast ships, efficient weapons, but also a strong power to penetrate, through corruption, the prevention and control systems.